2017
DOI: 10.1007/s11743-017-1995-z
|View full text |Cite
|
Sign up to set email alerts
|

Biosafety Evaluation of Three Sodium Lauryl N‐Amino Acids Synthesized from Silk Industrial Waste in Mice

Abstract: In this study, three amino acid mixtures recovered from silk industry waste were reacted with lauryl chloride to synthesize three sodium laurel N‐amino acid surfactants. The three types of anionic surfactants are referred to as silk fibroin surfactant, silk sericin surfactant, and silkworm pupae surfactant. All three surfactants showed good surface properties. To evaluate biological safety, we added these three surfactants to the normal diet of mice for 8 weeks. Blood indices, blood lipid, antioxidant capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For instance, Ding et al have shown no adverse effects for mixtures of N -AAA in mice diet at 5 wt%. 44 As proven by Perinelli, 45 N -lauroylserine or N -lauroylproline is not cytotoxic at concentrations as high as 1.5 wt%. These facts show the lack of innocuity of these compounds.…”
Section: Introductionmentioning
confidence: 93%
“…For instance, Ding et al have shown no adverse effects for mixtures of N -AAA in mice diet at 5 wt%. 44 As proven by Perinelli, 45 N -lauroylserine or N -lauroylproline is not cytotoxic at concentrations as high as 1.5 wt%. These facts show the lack of innocuity of these compounds.…”
Section: Introductionmentioning
confidence: 93%
“…Sericin is needed to be solved in the treatment of silk industrial waste, and the preparation of sericin protein surfactant provides a new solution for silk industry waste. The properties and synthesis of SSS have been studied in detail by our team (Wu & Zhang, 2014;Ding et al, 2017). In this article, for the first time, we describe the formation of catanionic vesicles, formed using the anionic surfactant (SSS) and a cationic drug.…”
Section: Introductionmentioning
confidence: 99%